1: Solve for either x or y in one of the equations. So x + y = -1 is y = -x -1
2: substitute the new equation in the opposite equation. So x - (-x - 1) = 7
3: distribute the negative. X + x + 1 = 7
4: combine like terms. 2x + 1 = 7
5: solve for x. Subtract 1 on both sides. 2x = 6
6: divide by 2 to get x by itself. X = 3
7: plug the new value of x into one of the ORIGINAL equations. 3 + y = -1
8: solve for y. Subtract 3 on both sides.
Y = -4
9: the solution is written as (x,y) so the solution would be (3, -4)
Answer:
x = 4
Step-by-step explanation:
Hello!
We can solve for x by expanding the parentheses and isolating x.
<h3>Solve for x</h3>
- 3x - 2(2x - 5) = 2(x + 3)-8
- 3x - 4x + 10 = 2x + 6 - 8
- -x + 10 = 2x - 2
- 10 = 3x - 2
- 12 = 3x
- x = 4
The value of x is 4.
Answer
63rrdddd
Step-by-step explanation:
X^2 + y^2 - x^2 +y^2
That would be (1x+1y)-(1x+1y)